The Influence of Government Expenditure on Education, Health and Poverty Sectors on Indonesia’s Human Development Index in 2019-2023 an Islamic Economics Perspective - Siti Chotifah Hastuty; Hayati, Mardhiyah; Ermawati, Liya (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2026)
This study aims to analyze the influence of government spending in the education, health, and poverty alleviation sectors on Indonesia's Human Development Index (HDI) for the 2019–2023 period. This study integrates fiscal policy analysis with an Islamic economic perspective. Particularly through the maqashid al-shariah approach, providing a distinct normative framework for evaluating the effectiveness of government spending on human development. The method used is a quantitative approach with regression of panel data based on secondary data from BPS-Statistics Indonesia and the Ministry of Finance. The results showed that education expenditure had a negative and insignificant effect on Human Development Index (HDI), health expenditure had a positive but insignificant effect, and poverty alleviation expenditure was also insignificant. Simultaneously, all variables had no significant effect on Human Development Index (HDI). This study concludes that increasing government spending has not been effective in increasing Human Development Index (HDI), so more targeted and efficient policies are needed.